The Role of Zakat, Infak, and Alms in Mediating the Influence of Internal and External Factors on MSME Sales Turnover - Nuzulul Qurnain; Zef Risal; Muhammad Herman Djaja (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of internal and external business factors on sales performance, with the practice of Zakat, Infaq, and Sedekah (ZIS) as a mediating variable. The study uses a quantitative approach with the Structural Equation Modeling – Partial Least Square (SEM-PLS) method. The research sample consists of micro, small, and medium enterprises (MSMEs) that implement religion-based philanthropic practices. Evaluation of the measurement model shows that all indicators have adequate outer loadings, so that the constructs of Internal Factors, External Factors, ZIS, and Sales Turnover can be comprehensively represented. The results of the structural model analysis indicate that both internal and external factors significantly influence ZIS practices, with external influences being more dominant. ZIS is proven to play a partial mediation role in the relationship between internal and external factors on Sales Turnover, which confirms that business philanthropic practices not only provide social value but also have a positive impact on economic performance. The coefficient of determination (R²) of ZIS is 0.532, and Sales Turnover is 0.620, indicating moderate to strong predictive ability of the model. The findings of this study extend the SEM-PLS literature by integrating internal, external, and religious philanthropy dimensions in explaining business performance. Practically, the study confirms that business actors can utilize ZIS as a strategy to enhance reputation, consumer trust, and competitive differentiation, thereby supporting business sustainability and competitiveness. This research provides implications for business actors, policymakers, and MSME support institutions to systematically integrate philanthropic practices into their business strategies.